3-dimensional computer graphics model elucidating involvement of intraparenchymal venous malformation in trigeminal nucleus of brachium pontis with intractable trigeminal neuralgia. (June 2020) - Yoshida, Shinsuke; Shin, Masahiro; Kin, Taichi; Saito, Nobuhito
Highlights: Venous malformation in the posterior cranial fossa can cause trigeminal neuralgia. Microvascular decompression of its drainer was effective only in the limited cases. Its pathological mechanism causing TN is controversial. Computer graphics elucidated the anatomic correlation of pontine trigeminal nucleus. Abstract: Venous malformation (VM) in the posterior cranial fossa occasionally cause trigeminal neuralgia (TN), which were treated with microvascular decompression of its drainer, whereas it was effective only in the limited cases, and its pathological mechanism causing TN is controversial. A 72-year-old man had a 20-year history of typical but severe TN in his left face. Without radiographic evidence of vascular compression on the root entry zone (REZ) of the trigeminal nerve, he underwent stereotactic radiosurgery in previous hospital, resulting in only temporary improvement. On T1-wighted magnetic resonance image with enhancement, the left trigeminal nerve was focally enhanced, which was typical finding after high dose irradiation for TN. Simultaneously, it disclosed small "caput medusa" within the pontine tegmentum, indicated existence of VM in brachium pontis. A 3-dimensional computer graphics model created by fusion of magnetic resonance angiography, diffusion tensor tractography, and fast imaging employing steady-state acquisition elucidated VM was located in the trigeminal nucleus of brachium pontis, which will be very useful for understanding the anatomic correlation of VM and pontine trigeminal nucleus. Since there was no vascular compression at the REZ of the trigeminal nerve, microvascular decompression was not indicated. With minimum dose of gabapentine and carbamazepin, his facial pain completely disappeared and controlled for more than 5 years.